Multicultural Education Curriculum in Preschool Education : (Kurikulum Pendidikan Multikultural dalam Pendidikan Prasekolah) - Indriani Puspita Hafidz (Tarbawi, 2022)
Multicultural or called as multiple cultures derive from a word multi which means more than one and cultural refers to culture. Multicultural means cultural diversity. The concept of multiculturalism or cultural diversity must be introduced as early as possible to the children because living amid that existence is so necessary for children to be able to accept it. Yet the problem now is that many teachers and schools find it difficult to implement multicultural education in schools. One of the main reasons is the lack of a multicultural education curriculum that can serve as a guidance in learning. This article will describe the concepts and characteristics of a multicultural education curriculum model. All are intended as alternative proposals for the preschool education curriculum. Meanwhile, Optional Reporting Items for Systematic Review and Meta-Analysis (PRISMA) were adopted for the current research review using two major journal databases, namely Scopus and Google Scholar. Thus, the search effort yielded a total of 9 articles that could be systematically analyzed from the various articles that had been excluded with filtering tailored to the specified criteria.